2022
DOI: 10.3390/cryst12111668
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Evolution of Morphology, Transport Properties for Bi2Te3 Nanoplates

Abstract: Bi2Te3 has an extensive application as thermoelectric materials. Here, large scale Bi2Te3 single-crystal hexagonal nanoplates(NPs) with size of 0.4–0.8 μm were synthesized successfully by hydro-thermal method. X-ray diffraction (XRD), scanning electron microscope (SEM), and transmission electron microscope (TEM) were used to characterize the Bi2Te3 nanoplates, which confirm the single crystal quality and smooth surface morphology with large size. We discussed the morphology-evolution in detail the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 74 publications
1
20
0
Order By: Relevance
“…The Bi 2 Te 3 rhombic lattice is represented by all diffraction peaks in the XRD data (JCPDS: 15-0863). The stylized peaks are readily correlated with the planes of the Bi 2 Te 3 rhombic lattice phases (015), (1,0,10), ( 110), ( 205), (0,2,10), and (1,1,15) [12,[19][20][21][22]26,50,[59][60][61][62][63][64].…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…The Bi 2 Te 3 rhombic lattice is represented by all diffraction peaks in the XRD data (JCPDS: 15-0863). The stylized peaks are readily correlated with the planes of the Bi 2 Te 3 rhombic lattice phases (015), (1,0,10), ( 110), ( 205), (0,2,10), and (1,1,15) [12,[19][20][21][22]26,50,[59][60][61][62][63][64].…”
Section: Resultsmentioning
confidence: 86%
“…Recent research has shown that ZT of thermoelectric materials typically stays around 1.0 [14][15][16][17][18][19][20]. The conversion efficiency of Bi 2 Te 3 is low, but low power applications are gradually gaining the attention of researchers [21][22][23][24][25][26][27][28]. Currently, a wide range of demands have been developed for low-power generation and cooling technologies, the applications of which primarily operate in room-or low-temperature environments, such as micro-motor power systems, IoT wireless sensing modules, and wearable intelligent samples [29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the Bi 2 Te 3 synthesis methods, the material was prepared successfully using techniques based on chemical reaction in solution, such as electroless deposition [ 6 ], electrochemical deposition [ 7 ], solvothermal [ 1 ], and sol–gel [ 8 ], among others. Such techniques require additional treatments to obtain a uniform and adherent thin film, free of secondary phases formed by the employed chemical precursors.…”
Section: Introductionmentioning
confidence: 99%